PHONOTACTIC AND PHONOLOGICAL SYSTEM IN KEMPO AND S>H KOLANG SUBDIALECTS - Salahuddin, Salahuddin; Winarti, Daru (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2023)
This study explores the phonological system in the Kempo subdialect (MSdK) and S>H Kolang subdialect (MSdS>H) in West Manggarai Regency. The study was conducted at nine survey sites by interviewing 200 vocabularies compiled by Swadesh. I analyzed the data by comparing the phonological systems between the two subdialects and formulating the possibilities of their occurrence in the word. The results show that the two subdialects have slightly different phonological systems. They have a different inventory of vowel phonemes: 15 consonant sounds in MSdK and 17 consonant sounds in MSdS>H. This study also found three non-pulmonic consonant phonemes in the two subdialects: bilabial /?/, Alveolar /?/, and Velar /?/. In the case of the two subdialects, the non-pulmonic consonant phonemes have unique characteristics: (1) appearing in the initial and middle positions of words, making it impossible for three pulmonic consonants (i.e., consonants /b/, /d/, and /g /) to appear in the initial position. The existence of the three consonant phonemes only appears when at the beginning of the word, it is preceded by another consonant forming a cluster and located on the first syllable (i.e., /mb/, /nd/, and /?g/). The two subdialects also have a relatively similar inventory of vocal phonemes: 6 vowel phonemes. Diphthongs are almost identical between the two subdialects, 7 diphthongs which only appear in mono-syllable words and are located at the end of words. In contrast, two additional diphthongs in MSdS>H appear in two-syllable words and the middle position of the word.